2017
DOI: 10.1016/j.actbio.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient delivery of potent anticancer iminoquinone derivative by multilayer hydrogel cubes

Abstract: We report a novel delivery platform for a highly potent anticancer drug, 7-(benzylamino)-3,4-dihydro-pyrrolo[4,3,2-de]quinolin-8(1H)-one (BA-TPQ), using pH- and redox-sensitive poly(methacrylic acid) (PMAA) hydrogel cubes of micrometer size as the encapsulating matrix. The hydrogels are obtained upon cross-linking PMAA with cystamine in PMAA/poly(N-vinylpyrrolidone) multilayers assembled within mesoporous sacrificial templates. The BA-TPQ-loaded hydrogels maintain their cubical shape and pH-sensitivity after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 83 publications
1
40
0
Order By: Relevance
“…Other types of MDM2 inhibitors, especially those that directly inhibit MDM2 itself, for example, SP141, JapA, and MA242, should be evaluated for their therapeutic efficacy and safety, as they may provide stronger activity by blocking both the p53‐dependent and p53‐independent functions of MDM2. Further evaluation and development of MDM2 inhibitors for cancer therapy are underway . These studies will provide proof‐of‐principle results to support the therapeutic value of this targeting strategy in drug discovery and may greatly contribute to the development of new therapeutics to treat noncancer diseases.…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 90%
“…Other types of MDM2 inhibitors, especially those that directly inhibit MDM2 itself, for example, SP141, JapA, and MA242, should be evaluated for their therapeutic efficacy and safety, as they may provide stronger activity by blocking both the p53‐dependent and p53‐independent functions of MDM2. Further evaluation and development of MDM2 inhibitors for cancer therapy are underway . These studies will provide proof‐of‐principle results to support the therapeutic value of this targeting strategy in drug discovery and may greatly contribute to the development of new therapeutics to treat noncancer diseases.…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 90%
“…In vitro experiments with the anticancer drug BA-TPQ (which is highly potent but with limited solubility, and hence has low bioavailability and toxicity) have demonstrated that drug-loaded hydrogel cubes are more potent against liver cancer cells than normal. Hydrogel cubes loaded with BA-TPQ can be delivered iv., as well as orally as experiments have shown [27].…”
Section: Hydrogel Cubesmentioning
confidence: 99%
“…Panc1 and HPAC cells were seeded in 6-cm dishes (3-5×10 5 cells/well) overnight and exposed to terphenyllin (20, 50, or 200 mM) or DMSO for 24 h. The treated cells were then lysed with RIPA buffer (Absin Bioscience Inc, Shanghai, China) containing protease inhibitors (Solarbio Science & Technology Co., Ltd., Beijing, China) and phosphatase inhibitors (Roche, Switzerland). The cell lysates were centrifuged and the supernatants were collected, quantified, separated by an SDS-PAGE gel, and transferred to a PVDF blotting membrane (GE Healthcare, USA) for Western blot analysis following the manufacturer's protocol (Xue et al, 2017;Qin et al, 2018). After blocking with 5% nonfat milk and incubation with primary and second antibodies, the blotting membranes were examined using ECL luminescence reagent (Absin, Shanghai, China), and the images were acquired on a FluorChem Q System (Alpha Innotech, Cell Bioscienes, USA).…”
Section: Western Blottingmentioning
confidence: 99%